The relationship between supplier control and competition in public sector outsourcing. (12th April 2018) - Johansson, Tobias; Siverbo, Sven
Abstract: The aim of this article is to develop theory and contribute to empirical studies about how the effectiveness of bureaucratic controls in public sector outsourcing is contingent upon supplier competition, and why and how this interaction plays out differently for hard and soft types of outsourced services. In previous inter‐organizational management control (IOMC) research there is a contradiction between theory and empirical results concerning how bureaucratic control and supplier competition interacts in aligning suppliers. While IOMC theory suggests competition reduces the need for bureaucratic control, empirical studies clearly indicate the opposite. We extend previous research and theorizing by differing between the outsourcing of hard and soft types of services and by testing the joint effect of bureaucratic control and competition on supplier alignment. The empirical case for testing theory is outsourcing by competitive tendering in the public sector. We use transaction level data from 166 local government suppliers in Sweden. In accordance with our prediction, the effect of bureaucratic control in aligning suppliers decreases with supplier competition when hard types of services are outsourced. For soft types of services, our results indicate that bureaucratic control is not contingent upon supplier competition. Furthermore, we show that when supplier competition is low the effect of bureaucratic control on supplier alignment is stronger for hard than for soft types of services. These results constitute an important contribution to the central notion of the interplay between bureaucratic control and competition in the IOMC literature.